Arquitetura de autoproteção para internet das coisas baseada no Laço MAPE-K - Mello, Ruan Marcos de Araujo Correia (2017)
The Internet of Things is a new paradigm based on Ubiquitous Computing or Pervasive Computing. Ubiquitous Computing and Pervasive Computing are terms used to describe the omnipresence of information technology in people’s daily lives. Its main goal is to create the possibility of communication between people and things and also between things without the need of human intervention. The Internet of Things environment has enough restrictions and the main one is the little computational resource of the devices. The little computational resource of the devices ends up resulting in a very insecure environment and conducive to various types of attacks, be they physical or logical. To make the Internet of Things environment more receptive and well-liked by all, it is important to invest in security. For this it is very interesting to associate security mechanisms with autonomic properties, considering the exponential growth of connected devices. This work proposes a security architecture focused on the Internet of Things environment. The proposed architecture has autonomic characteristics and is based on the MAPE-K Control Loop. In order to verify the effectiveness of the proposed architecture, it was approached some of the main attacks that occurred in the environment in question (Selective Forward, Blackhole, Sinkhole and Flooding). The impact of these attacks and their interference on the network operation created by the RPL routing protocol were analyzed.